Paul Tillich's Philosophical Theology - Pattison, George. author. aut Link
VIII, 118 p.
Keywords: Paul Tillich's Philosophical Theology takes up the challenge as to whether his thought remains relevant fifty years after his death. In opposition to those who believe that his writings have little to say to us today, this book argues that his thought is largely exemplary of open theological engagement with the contemporary intellectual situation.